The Musical Creativity of Senggol Tromol Semarang in The Context of Social Change - Apriadi, Sugeng; Wadiyo, Wadiyo (Catharsis, 2018)
Senggol Tromol is a parody music group from Semarang, most of their songs are representation of phenomenon which is trending in society for a certain period of time. The phenomenon would only last for a certain period of time because of social change happens in the society. The purpose of this study is to analyze the creative process and the social change which happen to Senggol Tromol. This study used qualitative method with observation, interview, and documentation as the method of collecting data. The methods of data analysis were data collection, data presentation, data reduction, and data verification. The results of the study show that in the creative process, Senggol Tromol did not always create new works, but they also modified existing ones. The steps were searching for inspiration, gathering ideas, determining the target listener, determining the themes, creating song structure and arrangement. The social change happens in Senggol Tromol went along with the presence of digital music platform which replaced physical release era, used by them as the promotion media to sell their works digitally.